(untitled) (Journal of the College of Basic Education, 2022)
This research aims to identify the effect of (learning grammatical concepts) and its acquisition by the learners of the second intermediate grade students). The researcher followed the experimental method, being the appropriate approach to the nature and goal of the research. The researcher chose one of the experimental designs with partial control, which is the design of the non-randomized control group with only the post-test, and the research community consisted of the day middle schools affiliated to the General Directorate of Education of Wasit Governorate / Al-Aziziyah Education Directorate, and the researcher chose from them the researcher Randomly (Mixed Martyr Ahd Intermediate) to be the research sample, as the total number of second-grade intermediate students was (120) students, divided into (4) sections, and the sample was chosen by a simple random method, which is Division (B) to represent the experimental group of (30) ) students, and class (c) to represent the control group, which numbered (30) students. The researcher rewarded the students of the two study groups statistically in the variables (chronological age calculated in months, academic achievement of fathers and mothers, intelligence test, and Arabic language subject scores for the previous academic year (2020-2021(. The researcher identified five topics from the Arabic grammar subject to be taught for the academic year (2021-2022) by the Ministry of Education for the second intermediate grade that he will study during the duration of the experiment. A group of experts and specialists were asked to judge its validity. In light of this, the necessary modifications were made, and the behavioral objectives and teaching plans in their final form were ready for implementation. The researcher prepared a concept acquisition test, with (21) items, of the type of objective questions (multiple choice) that measures the three levels (knowledge, understanding, and application) and its validity, difficulty factor, strength of discrimination, and stability were verified. The researcher applied the experiment on Monday, 11/13/2021, and it ended on Monday, 17/1/2022, and the grammatical concepts test was applied on Monday, 17/1/2022. The researcher studied the two study groups (experimental and control) himself. The researcher used the following statistical methods (the t-test, the square (Ka2), the intelligence test, the difficulty coefficient, the discrimination coefficient, the Facronbach equation - and the effectiveness of the wrong alternatives). After analyzing the results of the students’ answers and treating them statistically by using the T-test for the middle samples to find out the significance of the difference at the level (0.05) between the two study groups, the following became clear: There is a statistically significant difference at the level of significance (0.05) between the mean scores of the experimental group students who are studying Arabic grammar in a manner (Learning grammatical concepts and their acquisition by the learners) and the average scores of the control group students who study Arabic grammar in the traditional way in a test of acquiring grammatical concepts for the benefit of the experimental group.